Assessment of sperm cryopreservatives and oocyte vitrification for In vitro embryo production in cattle - Ghareeb, Salman Hammadi (2017)
Animal breeding programmes and assisted reproductive techniques (ART) such as artificial insemination (AI), embryo transfer (ET) and intra-cytoplasmic sperm injection (ICSI) are extremely dependant on the quality of sperm and oocytes used. Furthermore, fertility ratios still need to be improved particularly those related to the cryopreserved sperms and vitrified oocyte. In this study, a number of experiments were carried out to improve the quality of cryopreserved semen and vitrified immature oocytes and evaluation of in vitro embryo production as well. Seven bull semen extenders were prepared and used to extend a total of 102 ejaculates that were collected from twelve mature healthy fertile Brangus-Herford bulls by automatic electro-stimulation at the animal farm of the Universiti Putra Malaysia. On the other hand, 180 ovaries were collected from slaughtered local cattle at Banting Abattoir, Malaysia. Post-thaw semen evaluation were evaluated for the extending capacity of seven different types of extenders implemented in bull semen cryopreservation; these extenders were AndroMed®, BioXcell®, Triladyl®, Tris-egg yolk based extenders 20%, Tris-egg yolk plasma with concentration of 10%, Tris-egg yolk plasma with concentration of 15 % and Tris-egg yolk plasma with concentration of 20% on the sperm’s motility, viability, morphology, DNA integrity, plasma membrane integrity and acrosome integrity. Also, the cryopreservation process was conducted in two regimes of fresh semen preparation prior to subjecting to cryopreservation. These were seminal plasma being removed from fresh semen samples and fresh semen samples with their seminal plasma. Semen samples were collected using electrical stimulation by an automatic electro-ejaculator (AEE), and semen quality was analysed using computer assisted semen analyser (CASA). The Eosin-Nigrosine staining technique was applied to evaluate the morphology, viability and acrosome intergrity. The DNA integrity was evaluated using a modified Acridine orange method. Amongst the three commercial extenders, AndroMed®, BioXcell®, Triladyl® and the Tris-egg yolk based extenders, the AndroMed® extender produced the highest extending capacity to the sperm’s motility, morphology, DNA integrity, plasma membrane integrity and acrosome integrity. BioXcell® and Tris-egg yolk based extenders had the best capacity to protect the sperm’s viability. These results, therefore, favour AndroMed® over the rest of the other extenders used in post-thaw sperm parameters with seminal plasma. The AndroMed®, Triladyl® and Tris –egg yolk extender were highest in extending capacity than BioXcell® at the level of post-thaw semen evaluation and preserving semen without seminal plasma. Among the egg yolk extenders, the egg yolk plasma extender 10% produced the highest extending capacity to the semen plasma membrane integrity, viability, and motility, while the Tris-egg yolk based extender 20% and Tris-egg yolk plasma 10% had the best capacity to protect the semen’s morphology and acrosome integrity. These results, therefore, favour the concentration of Tris-egg yolk plasma 20% over the rest of the other extender concentration egg yolk used in extending ejaculated semen with seminal plasma. In the study that involved seminal plasma removal, the spermatozoa was also evaluated for its qualities using Tris-egg yolk based extenders 20%, Tris-egg yolk plasma with concentration 10% , Tris-egg yolk plasma with concentration 15% and Tris-egg yolk plasma with concentration 20%. The egg yolk plasma with concentration 15% extender gave a better extending capacity to the semen viability and acrosome integrity, while Tris-egg yolk based extender 20% had the best capacity to protect the semen’s morphology and plasma membrane integrity. This result, therefore, favours the concentration of the egg yolk plasma with concentration 15% and Tris-egg yolk based extender 20% over the rest of the other extender concentrations of egg yolk plasma. In the immature oocyte study, oocytes were harvested from bovine ovaries collected from local abattoir (Banting, Malaysia), then transported in thermos containers at 37°C (phosphate buffer saline) to the Theriogenology and Cytogenetic laboratory within 2- 3 hours post-slaughtering. Slicing method of ovaries were applied to harvest the immature oocytes. Pipetting of the considered oocytes was done from the handling medium into the washing medium. This study aimed to study the effect of different vitrification exposure times of 15 sec, 30 sec and 45 sec of immature bovine oocytes and their ability to fertilise and produce an embryos after application of In vitro fertilisation technology. Ethylene Glycol (EG) and Dimethylsulfoxide (DMSO) were used as a combination of two cryoprotectants. Two main cryodevices were also used; they were open pulled straws (OPS) and closed French straws (CFS). OPS were modified locally by using hot plate and pulled manually. Vitrified-warmed immature oocytes were evaluated morphologically under epiflourocent microscopy. The viable oocytes were subjected into the maturation media, mainly composed of TCM199+HEPES supplemented with 10% FCS and 10 ng/ml epidermal growth factor (EGF). Polar body extrusion was observed 22 hr post IVM. In vitro fertilization (IVF) was applied using direct infusion of frozen-thawed bull semen extended in AndroMed® (as the best extender described in first experiment; Chapter Four). The frozen-thawed bull semen was collected at the bottom of Percoll solution (45% over 90%) then washed in Tyrodes medium. The viable spermatozoa were diluted in the appropriate volume of fertilization medium to achieve a final concentration of 2×106 sperm/ml. A 250 μl aliquot of this suspension was added to each well containing oocytes for a final concentration of sperm cells of 1×106 sperm/ml. Spermatozoa and oocytes were co-incubated for 18-22 h at 38.8 °C in a humidified atmosphere of 5% CO2 in air. For in vitro culture (IVC) presumptive zygotes were vortexed and washed three times in HEPES-buffered TCM199 containing 0.4 g/l BSA and 4 μg/ml gentamicin, to remove cumulus cells and attached spermatozoa. Zygotes were washed two times in SOF medium supplemented with BME amino acids (50×), MEM amino acids (100×), 3 mM pyruvate, 6 mg/ml fatty acid free BSA and 5% FBS and transferred by groups of 25 into four-well petri dishes containing 50 μl drops of culture medium covered with 700 μl of mineral oil. This study showed that the immature bovine oocytes can be vitrified at the GV-stage with our optimized protocol and that the vitrified-warmed GV-oocytes could be matured and in vitro fertilized and subsequently in vitro embryo development. Also, the vitrification of bovine immature oocytes in the solutions composed of 15% EG + 15% DMSO using OPS method achieved the best viability, the highest maturation, and cleavage in our conditions after IVM and IVF despite a lower recovery rate than the other group. Data were analysed using SPSS software system (Version 12.0, SPSS, Chicago, IL). Study parameters were analysed using a 2-way factorial analysis of variance (ANOVA). Values were expressed as mean ± standard error of the mean (S.E.M). The level of statistical significance was at P<0.05.